A large-deformation random finite-element study: failure mechanism and bearing capacity of spudcan in a spatially varying clayey seabed. Issue 5 (21st May 2019) - Yi, Jiang Tao; Huang, Li Ying; Li, Dian Qing; Liu, Yong
Abstract : Although the random heterogeneity of a clayey seabed has been long recognised, it is relatively recently that the influence of spatial variability on the spudcan foundation has been explicitly explored by random finite-element analyses. Owing to technical and computational challenges, these are still limited to the small-strain Lagrangian finite-element calculation with the 'wished-in-place' assumption, which is a departure from the reality. Attempts were successfully made in this research to combine the large-deformation finite-element calculation with random field theory in a Monte Carlo simulation framework. The continuous penetration of a spudcan in a clayey seabed was modelled through the coupled Eulerian–Lagrangian finite-element calculation with simultaneous consideration of the strain-softening effect and linearly increasing strength with depth. The results suggest that the randomness of soil strength can obviously alter the flow pattern and failure mechanism of soil, and in turn affects the bearing capacity of the spudcan. The log-normal probability distribution function was found to fit the distribution of the bearing capacity factor well. A correlation between the failure probability and the safety factor was established, from which the level of reliability corresponding to different safety factors can be clearly evaluated. Such a correlation may facilitate the further development of reliability-based design.